PENGARUH PENAMBAHAN UREA DAN MELAMIN PADA PEREKAT UREA FORMALDEHIDA TERHADAP EMISI FORMALDEHIDA DAN KETEGUHAN REKAT TRIPLEKS MERANTI - Paribotro Sutigno; Adi Santoso (Jurnal Penelitian Hasil Hutan, 1995)
The problem in using plywood bonded with urea formaldehyde (UF) is formaldehyde emission, especially in a room with limited ventilation. To reduce formaldehyde emission, the glue can be mixed with catching agent. In this paper the effect of urea and melamine as catching agent on formaldehyde emission and on bonding strength of UF bonded plywood made from red meranti (shorea. spp) is discussed.The effect of catching agent type on formaldehyde emission is not significant while the effect of percentage of catching agent is highly significant on formaldehyde emission. The higher percentage of catching agent, the lower formaldehyde emission of plywood.The effect of catching agent type on plywood bonding strength is not significant, but the effect of percentage of catching agent is highly significant. The higher percentage of urea the lower plywood bonding strength, while the higher percentage of melamine and urea-melamine cause the higher plywood bonding strength. To meet formaldehyde emission of 0.165 ug/ml, it is recomended to use 10% urea on the weight basis of liquid UF.